Evaluation and Management of the Pediatric Patients with Suspected Gastroesophageal Reflux Diseases - Badriul Hegar; Yvan Vandenplas (The Indonesian Society for Digestive Endoscopy, 2011)
Gastroesophageal reflux is a normal physiologic process occurring in healthy infants. Symptoms due to gastro-esophageal reflux diseases (GERD) are troublesome when they have adverse effects on the well- being of the patient. A thorough history and physical examination is generally sufficient to establish a clinical diagnosis of uncomplicated infant with gastroesophageal reflux. Poor weight gain is a warning sign. Irritability and regurgitation are associated with a wide range of physiologic and pathologic conditions. Heartburn or substernal burning is a reliable indicator for GERD in adolescents. Barrett esophagus does occur in children with severe chronic reflux. GERD is commonly cited as a cause of dysphagia; however, there are no strong pediatric data demonstrating this relationship. An etiologic role for reflux in reactive airways disease, such as asthma, has not been established. No test can determine whether reflux is causing recurrent pneumonia. Data showing the correlation between reflux and upper airway disease is weak, consisting mainly of case descriptions. Sandifer syndrome is an uncommon, but specific manifestation of GERD. Children with cerebral palsy are at particularly high risk of GERD. Similarly, children with certain genetic syndromes such as Cornelia de Lange and Down syndrome are prone to GERD. A higher prevalence of GERD and its complications has been reported in patients with a variety of chronic respiratory disorders including bronchopulmonary dysplasia and cystic fibrosis. GERD treatment is frequently administered to premature infants. However, the true prevalence of GERD is unknown. Keywords: gastroesophageal reflux diseases, infants, children